Review of the materials of the All-Russian scientific and practical conference (with international participation) "Current directions of anti-corruption policy in solving the problems of national security of the Russian Federation", dedicated to the 10th anniversary of the creation of the Scientific and Educational Center for Anti-Corruption Legal Policy in the North Caucasus Federal District - A. P. Mazurenko (Современная наука и инновации)
This article is a review of the materials of the All-Russian scientific and practical conference (with international participation) "Current directions of anti-corruption policy in solving the problems of national security of the Russian Federation", dedicated to the 10th anniversary of the establishment of the Scientific and Educational Center for Anti-Corruption Legal Policy in the North Caucasian Federal District. Where current issues of combating corruption were considered, as one of the main threats to the national security of the Russian Federation. The author analyzed the most relevant reports, and outlined the main directions of the anti-corruption component of the North Caucasian Federal District.